Analisis Pengaruh Jenis Buku Terhadap Minat Baca Mahasiswa di Perpustakaan Ibrahimy dengan Algoritma K-Means Clustering - Mahmudi Mahmudi; Zaehol Fatah (CV. ALIM'SPUBLISHING, 2025)
In today's digital era, students' interest in reading seems to be declining, particularly in literacy activities aimed at enhancing knowledge. This issue has become a concern in efforts to foster a reading culture among students. This study aims to analyze and describe the types of books that can influence students' reading interest. Data were collected through student evaluations, lecturers' opinions, and librarians' perspectives. The data collection methods included questionnaires, observations, and interviews, with data analysis conducted through reduction processes. The study results highlight four main points: 1) The types of books that attract students' interest include fiction and non-fiction books. 2) External factors influencing reading interest include the environment, support from lecturers, and available facilities. 3) From librarians' perspectives, students' reading interest is affected by curiosity, available facilities, and academic assignments. 4) Efforts to enhance students' reading interest can be carried out through activities such as library visit competitions and book review contests. In conclusion, two types of books—fiction and non-fiction—can influence students' reading interest. A survey of 100 students revealed that 75% preferred fiction books, while the remaining 25% favored non-fiction books.